Assessment of cyber abuse in sexually abused children and adolescents - Çıkılı Uytun, Merve; Özmen, Sevgi; Demirci, Esra (The European Research Journal, 2019)
Objectives: Child sexual abuse is associated with adverse outcomes, including increased vulnerability, that may explain the risk of revictimization via cyber media and cyber abuse may be a risk factor for sexual abuse. The aims of the study were to explore cyber abuse prevalence in sexual abuse cases, the direct and indirect links between child sexual abuse and cyber abuse and to study the differences in internet use between children and adolescents who were sexually abused and the control group. Methods: We assessed 75 children and adolescents aged 7-18 who had experienced sexual abuse and were referred to us between 01.01.2014-01.01.2015. Additionally, 45 typical developing subjects who did not have any abuse history were recruited from pediatrics clinic of or hospital as the control group. We used our semi-structured questionnaire to assess cyber abuse. Results: The rates of internet use were high in the control group (97.8%) compared to those of sexually abused teens (82.7%). However, the rates of cyber abuse were similar between the groups. The most used web site/application was different between the groups. Facebook was the most used web site/application in the sexually abused group (69.4%). This ratio was only 20.5% in the control group. Conclusions: We assessed cyber abuse in a population exposed to sexual abuse. As several authors have previously emphasized, the implementation of preventative steps is essential. There is a great need to develop and evaluate interventions with those children and young people, particularly in sexually abused children and adolescents who are thought to be more vulnerable to cyber abuse.